ASEAN’s Digital Integration: Strategic Management, Challenges, Opportunities, and the Role of New Technologies - Suseno Hendratmoko (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objective of this study is to provide insight into the potential impact and implications of digital integration on the socio-economic landscape of ASEAN countries. Data sources for this study include an extensive literature review, statistical data from ASEAN reports, and peer-reviewed articles. The selection and extraction of data involved a rigorous process, ensuring that the most relevant and credible information is used. The data was then synthesized to provide a holistic understanding of the subject. The study concludes that although digital integration in ASEAN faces several challenges such as the digital divide, data privacy issues, and cybersecurity threats, it also offers significant opportunities for economic growth, innovation, and improved governance. The role of new technologies, such as artificial intelligence and blockchain, is vital and can help in mitigating challenges and harnessing opportunities. However, efficient strategic management is essential to effectively realize digital integration's potential benefits.